2015
DOI: 10.1093/nar/gkv394
|View full text |Cite
|
Sign up to set email alerts
|

MDC1 functionally identified as an androgen receptor co-activator participates in suppression of prostate cancer

Abstract: Mediator of DNA damage checkpoint protein 1 (MDC1) is essential for DNA damage response. However, the role of MDC1 in modulating gene transcription independently of DNA damage and the underlying mechanisms have not been fully defined. Androgen receptor (AR) is the central signaling pathway in prostate cancer (PCa) and its target genes are involved in both promotion and suppression of PCa. Here, we functionally identified MDC1 as a co-activator of AR. We demonstrate that MDC1 facilitates the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 59 publications
1
46
0
Order By: Relevance
“…MDC1 effectively co-activated ERα-mediated transactivation functions, and down-regulation of MDC1 expression resulted in a significant inhibition of ERα actions. On the other hand, our recent studies have demonstrated that MDC1 also associates with AR and co-activates AR-mediated transactivation via increasing the recruitment of histone acetyltransferase GCN5 46 . Thus, in addition to the role of MDC1 in DNA damage checkpoint, our findings provide the new function of MDC1 on modulation of steroid hormone receptor-mediated transcriptional activity.…”
Section: Discussionmentioning
confidence: 94%
“…MDC1 effectively co-activated ERα-mediated transactivation functions, and down-regulation of MDC1 expression resulted in a significant inhibition of ERα actions. On the other hand, our recent studies have demonstrated that MDC1 also associates with AR and co-activates AR-mediated transactivation via increasing the recruitment of histone acetyltransferase GCN5 46 . Thus, in addition to the role of MDC1 in DNA damage checkpoint, our findings provide the new function of MDC1 on modulation of steroid hormone receptor-mediated transcriptional activity.…”
Section: Discussionmentioning
confidence: 94%
“…Further, in patients with cervical cancer, an increased expression of MDC1 protein expression was found to be associated with tumorigenesis (20). Further, a recent study showed MDC1 knockdown leads to tumor progression in prostate cancer by revealing its function as DNA damage checkpoint factor in the cellular response to double-strand breaks by regulating G2/M transition (25). In accordance, Patel et al (22) in 2011 also showed reduced expression of nuclear MDC1 protein may serve as a prognostic marker in early-stage breast cancer for nodal recurrence when treated with surgery and radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have implicated MDC1 in regulating ER, wherein MDC1 directly binds to and increases the transactivation potential of ER, and also resides at sites of ER activity on chromatin. Interestingly, MDC1 levels decrease as a function of BrCa progression, and knockdown of MDC1 results in increased tumorigenic phenotypes, suggesting that the MDC1-dependent ER transcriptional program actually blocks cancer progression [61, 62]. Based on the studies outlined above, part of the functional output of the DDR machinery is to positively regulate ER function (table 1).…”
Section: Dna Repair Factors As Modulators Of Steroid Receptor Functionmentioning
confidence: 99%
“…Also, the MDC1-dependent AR transcriptome serves an anti-tumorigenic role, as MDC1 levels decrease with PCa progression, and knockdown of MDC1 results in increased cancer-associated phenotypes [62]. Given the roles of both ER and AR in tumor initiation and progression in BrCa and PCa, respectively, it will be of relevance to further dissect the mechanisms by which MDC1 seemingly renders the function of these NRs anti-tumorigenic.…”
Section: Dna Repair Factors As Modulators Of Steroid Receptor Functionmentioning
confidence: 99%